Student Self-Screening for Methicillin-Resistant Staphylococcus Aureus (MRSA) Nasal Colonization in Hand Hygiene Education - Lum, Tia (American Journal of Pharmaceutical Education, 2014)
Objective. To determine the feasibility and effectiveness of adding a hand hygiene exercise in self-screening for Methicillin-Resistant Staphylococcus Aureus (MRSA) nasal colonization to a health care delivery course for first-year pharmacy (P1) students. Design. About one month after students were trained in hand hygiene technique and indications, faculty members demonstrated how to self-screen for MRSA nasal colonization. Students were then asked to screen themselves during the required class time. Aggregated class results were shared and compared to prevalence estimates for the general population and health care providers. Assessment. The 71 students present in class on the day of the self-screening exercise chose to participate. A survey comparing presecreening and postscreening responses indicated incremental improvements in student knowledge and awareness of health care associated infections and motivation to perform hand hygiene. On the written exam, student performance demonstrated improved knowledge compared to previous class years. Conclusion. Self-screening for MRSA nasal colonization in a health care delivery course for P1 students increased students’ motivation to perform hand hygiene techniques and follow indications promulgated by the World Health Organization.